2022
DOI: 10.3390/app12020611
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of the Application of Different Commercial Software for Topology Optimization

Abstract: Topology optimization (TO) has been a popular design method among CAD designers in the last decades. This method optimizes the given design domain by minimizing/maximizing one or more objective functions, such as the structure’s stiffness, and at the same time, respecting the given constraints like the volume or the weight reduction. For this reason, the companies providing the commercial CAD/FEM platforms have taken this design trend into account and, thus, have included TO in their products over the last yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 73 publications
(39 reference statements)
0
10
0
1
Order By: Relevance
“…III. Software Review Tyflopouls and Steinert [12] have analysed different stand-alone and integrated software for topology optimisation purposes. They reported that about 31% of software is released under open source licence and freely available for users.…”
Section: Computer-aided Topology Optimisation Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…III. Software Review Tyflopouls and Steinert [12] have analysed different stand-alone and integrated software for topology optimisation purposes. They reported that about 31% of software is released under open source licence and freely available for users.…”
Section: Computer-aided Topology Optimisation Methodsmentioning
confidence: 99%
“…To solve the optimisation problem [10], several algorithmic approaches, such as solid isotropic material with penalisation (SIMP) or level set function (LSF), are developed and included into majority of today's computer-aided topology optimisation software [11]. Topology optimisation software, whether integrated into software or standalone [12], follows a defined methodological approach that generates a geometrical structure with an optimal density distribution after several iteration runs. In this paper, three topology optimisations included in Ansys Mechanical [13]- [18], Fusion360 [19]- [24], Solidworks Simulate [25]- [29], and stand-alone nTopology [30]- [33] are analysed and compared in terms of implementation and performance capabilities.…”
Section: Introductionmentioning
confidence: 99%
“…Among the algorithms used for topological optimization, such as homogenization [29], SIMP [30], ESO [31], and the RAMP approach [32], SIMP and RAMP methods are the most popular. While the SIMP method implies high efficiency in a narrow range of problems, the RAMP method is a stable method that can be used in a wider class of problems [33]. Therefore, the authors of this paper used the RAMP method.…”
Section: Statement Of the Topological Optimization Problemmentioning
confidence: 99%
“…Because of the growing interest in design for additive technologies, topology optimisation or other mathematical designing methods are implemented into standard CAD software. The main advantage is that the software does not require programming language knowledge, making it more suitable for a wider group of designers [ 9 ].…”
Section: Introductionmentioning
confidence: 99%